Profitability off Islamic banks in Malaysia / Muhammad Irfan Izzuddin Rozimin - Rozimin, Muhammad Irfan Izzuddin (2019)
The developing of Islamic banking system has made Malaysia become one of the most important centres in the world. This study is to identify the profitability of Islamic banks in Malaysia. The data is taken in this study is from 2009 until 2018. The sample data derived from the financial statement of 10 Islamic banks in Malaysia The data use Profitability of Islamic Banks in Malaysia as the dependent variable. Independent variables is used in this study are capital adequacy, return on asset, bank size and inflation rate. As for run data, this paper used Descriptive Statistic, Pearson Correlation, Regression Model, Correlation Coefficient and Multicollinearity test. The result found that return on asset, capital adequacy and bank size has positive relationship with profitability of Islamic Banks. On the other hand, inflation rate have positive relationship but insignificant with the profitability of Islamic bank.